2009
DOI: 10.1128/mcb.01709-08
|View full text |Cite
|
Sign up to set email alerts
|

SRp20 and CUG-BP1 Modulate Insulin Receptor Exon 11 Alternative Splicing

Abstract: The insulin receptor (IR) exists as two isoforms, IR-A and IR-B, which result from alternative splicing of exon 11 in the primary transcript. This alternative splicing is cell specific, and the relative proportions of exon 11 isoforms also vary during development, aging, and different disease states. We have previously demonstrated that both intron 10 and exon 11 contain regulatory sequences that affect IR splicing both positively and negatively. In this study, we sought to define the precise sequence elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 51 publications
(51 reference statements)
8
109
1
Order By: Relevance
“…SRSF3 functions in both alternative splicing and mRNA transport to the cytosol (35,36). Our data suggest that SRSF3 is regulating splicing of G6PD mRNA rather than transport because the loss of SRSF3 decreased the accumulation of spliced RNA (Figs.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…SRSF3 functions in both alternative splicing and mRNA transport to the cytosol (35,36). Our data suggest that SRSF3 is regulating splicing of G6PD mRNA rather than transport because the loss of SRSF3 decreased the accumulation of spliced RNA (Figs.…”
Section: Discussionmentioning
confidence: 78%
“…In this regard, members of the hnRNP family of splicing silencing proteins, K, L, and A2/B1, bind to the G6PD regulatory element in the starved state, and this binding is decreased by refeeding (19). Competition between SRSF3 and splicing silencers has been demonstrated in regulation of the alternative splicing of the insulin receptor (36). A similar competition for binding may be part of the regulatory mechanism controlling G6PD splicing in response to nutrients and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies indicate that CUGBP1 may be involved in metabolic disorders. CUGBP1 has been reported to mediate alternative splicing of the insulin receptor [27] and to contribute to insulin resistance [28]. Verma et al showed that CUGBP1 is upregulated in the hearts of diabetic mice [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such double-stranded stem-loop RNA structures are recognized by trans-acting factors and the whole complex lead to changes in mutual spatial distribution of cis-acting elements in this way forming additional regulatory "possibilities" [18,45,53]. Further studies investigating the alternative splicing of the insulin receptor has led to the identification of ISE and ISS elements in intron 10, as well as to better understanding of its mechanism [133,158]. In addition, SRp20 and SF2/ASF have been shown to modulate exonic enhancer elements (ESE) activity.…”
Section: Insulin Receptor Transcript's Characteristicsmentioning
confidence: 99%